Another new species of the genus Phyllodesma (Phyllodesma) Hübner, [1820] 1816 from northern China (Lepidoptera: Lasiocampidae) - Zolotuhin, Vadim V.; Bidzilya, Oleksiy V.; Kostjuk, Igor Yu. (Zootaxa, 2021)
Phyllodesma permana sp. nov. is described from wastelands of northern China (Ningxia Hui AR). A new species is compared with Phyllodesma sinina (Grum-Grshimailo, 1891), Phyllodesma jurii I. Kostjuk, 1992 and Phyllodesma mongolicum I. Kostjuk & Zolotuhin, 1994. Adults and male genitalia of two latter species are illustrated, and the differences among these taxa and Ph. permana sp. nov. are discussed. The holotype will be deposited in the Insect collection, College of Life Sciences, Nankai University (Tianjin, China). A list of the nowadays known from China Phyllodesma is given.